2019
DOI: 10.1002/jclp.22877
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intrapersonal emotional competences on the relationship between attachment insecurity and severity of eating disorder symptoms in patients with restrictive anorexia

Abstract: Objective Attachment insecurity and emotional competences (EC) form a key part of conceptual models of anorexia nervosa (AN). We explored the relationship between attachment dimensions and EC on the severity of eating disorders in patients diagnosed with restrictive AN. Method Sixty‐three female patients with restrictive AN and 63 healthy participants completed self‐report measures (eating symptoms, EC, attachment, depression, and anxiety). Result Patients with restrictive AN used fewer adaptive and more malad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
1
4
0
1
Order By: Relevance
“…The results of the study by Nalbant et al (2020) showed lower levels of secure attachment in the AN clinical sample. Nandrino et al (2020) observed in their AN sample a greater presence of anxious and avoidant IAS, in addition to lower competencies for intrapersonal emotional management skills compared to the HC. Batista et al (2018) found higher levels of anxious and avoidant IAS in the sample with AN than in the healthy control group (HC).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…The results of the study by Nalbant et al (2020) showed lower levels of secure attachment in the AN clinical sample. Nandrino et al (2020) observed in their AN sample a greater presence of anxious and avoidant IAS, in addition to lower competencies for intrapersonal emotional management skills compared to the HC. Batista et al (2018) found higher levels of anxious and avoidant IAS in the sample with AN than in the healthy control group (HC).…”
Section: Resultsmentioning
confidence: 92%
“…The studies show a clear association between IAS and AN, in some cases offering mediating variables, such as alexithymia (Redondo & Luyten, 2018) and obsessive–compulsive rigidity (Amianto et al, 2021). There are other elements to consider, such as the recommendation of a transdiagnostic approach in the study of EDs (Monteleone et al, 2017), lower intrapersonal skills and interpersonal management (Nandrino et al, 2020), and the limited study of the relationship between disorganized IAS and AN or other ED.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ez azonban a leginkább az evéssel, a testsúllyal, az alakkal kapcsolatos rágódásra vonatkozik, míg a CERQ nem specifikus ezekre a tünetekre, így elképzelhető, hogy a korábbi vizsgálatokban -más eszközökkel mért -ruminatióra vonatkozó különbség a jelen esetben nem tudott megmutatkozni. Nandrino és munkacsoportja [38] vizsgálatában -mely CERQ-t használt felnőtt nők körébenaz AN-diagnózisú személyek, bár szignifikánsan többet alkalmazzák a ruminatiót az egészséges kontrollcsoporthoz képest, csak csekély hatásméretet tudtak kimutatni. Mindemellett a jelen kutatás alapján felmerülhet a kér- dés, hogy a két, krónikus betegek alkotta csoport miért használ kevesebbet ebből a stratégiából, valamint a 'mások hibáztatása' stratégiából a testileg egészséges társaikhoz képest.…”
Section: Megbeszélésunclassified
“…As the experiences of family conflicts and conflicts that the child witnesses in the family become permanent, the emotional insecurity of the child in later periods becomes ingrained (Li et al, 2020 ). This situation may cause many psychopathologies in other stages of the developmental period (Liese et al, 2020 ; Liu et al, 2020 ; Nandrino et al, 2020 ). On the contrary, children who gain trust in the family experience positive life patterns and positive moods in later periods (Hoffman et al, 2017 ).…”
Section: Emotional Security Forgiveness and Happinessmentioning
confidence: 99%